Hat die Elektromobilität eine Zukunft? - Thomas Döring (Wirtschaftsdienst, 2012)
Als klimaschonende Alternative hat die Elektromobilität an Aufmerksamkeit gewonnen. Aus ökonomischer Sicht sind jedoch nicht allein die ökologischen Effekte von Elektrofahrzeugen kritisch zu beleuchten. Ob sie sich durchsetzen werden, hängt dabei sowohl von technischen Entwicklungen als auch von den Preisen der benötigten Rohstoffe, der einzelnen Module, der Strompreise, aber auch den Opportunitätskosten ab. Es fehlen gesicherte Erkenntnisse, mit welchen gesamtwirtschaftlichen Wirkungen zu rechnen ist. – – The paper focuses on whether e-mobility has a feasible chance of market penetration and social acceptance from an economic point of view. This includes a critical assessment of the ecological benefits as well as the other advantages of e-mobility. Furthermore, the likelihood of consumers switching from conventional vehicles to e-vehicles is considered by taking into account the opportunity costs related to such a substitution. Finally, additional macro-economic considerations show that factors such as the development of the battery market as well as increasing oil prices determine the prospective competitiveness of e-vehicles and subsequent structural changes within the mobility sector significantly.
Keywords: L91; Q55; R41; 330; Elektrofahrzeug; Opportunitätskosten; Stromtarif; Technischer Fortschritt; Verkehrsmittelwahl; Deutschland